Penggunaan Encapsulated Ice pada Thermal Energy Storage Sistem Chilled Water Dengan Laju Aliran Udara Bervariasi - Mainil, Rahmat Iman; Yandra, Vicky; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Air flow rate of Fan Coil Units (FCU) can affect cut off pump time in an air conditioning system, with controling air flow distribution to realization thermal comfort conditions in a residential building. With using secondary cycle of chiller system, a pump working for circulating chilled water through a FCU, for cooling system by Encapsulated Ice and water in Thermal Energy Storage (TES). A half of valve be opened for circulating volume flow rate of chilled water as normal condition. The thermostat use to controling room temperature at 26°C manually. The objective of this current study is to observ cut off pump power consumption. The Experiment is running in 8 hours with variations air flow rate 1.234 m/s and 2.432 m/s. The overall resultsshow that power consumption of pump can reduce around 15.11 % and 31.25%.Keywords: Encapsulated Ice, TES, Chiller.